Culture-forming role of the European bison (European Bison Conservation Newsletter, 2008)
The aim of the paper was to demonstrate a profound connection of European bison with culture and even, in a sense, with history. Presented is the incidence of representations of the European bison in various fields of art, in literature and music in chronological order, from ancient times until today. It shows that the motif of a bison constantly appears in texts of culture, as this animal from immemorial times fascinated humans with its power, majesty, beauty and wildness. Shrouded in mystery, the bison has been inspiring cultural activity and exciting imagination which became materialised in sculpture, painting, woodcut, photography, drawings, literature and music. Those works enrich our culture and prove how often artists showed fascination with the bison. The European bison is still present in common imagination of Poles and its image accompanies us in everyday life in a form of company logos, an alcohol brand, gifts, souvenirs, and is even present in mass media such as TV commercials. Its contemporary representations refer to the symbolism of a bison, shaped by history, tradition and beliefs. Bison is intrinsically linked to the culture and history of Poland, of which it became the pride and symbolic animal.
Keywords: Euroepan bison; culture